2023
DOI: 10.1186/s12986-022-00723-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular lipidomics analysis reveales increased levels of phosphocholine and lysophosphocholine in atherosclerotic mice

Abstract: Objective Atherosclerosis (AS) is the major cause of cardiovascular disease, and dyslipidemia is a principal determinant of the initiation and progression of AS. Numerous works have analyzed the lipid signature of blood, but scarce information on the lipidome of vascular tissue is available. This study investigated the lipid profile in the aorta of ApoE−/− mice. Method ApoE−/− mice were randomly divided into two groups: (1) the normal diet (ND) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Furthermore, the combination of PC(32:0) plasma levels and six other PC and Cer species was proposed as a novel risk score for cardiovascular death in coronary artery disease patients [51]. A vascular lipidomics study in atherosclerotic mice demonstrated an increase of certain PC species, including PC(34:1), in the plaque of mice on a high-fat diet compared to mice on a normal diet [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the combination of PC(32:0) plasma levels and six other PC and Cer species was proposed as a novel risk score for cardiovascular death in coronary artery disease patients [51]. A vascular lipidomics study in atherosclerotic mice demonstrated an increase of certain PC species, including PC(34:1), in the plaque of mice on a high-fat diet compared to mice on a normal diet [52].…”
Section: Discussionmentioning
confidence: 99%
“…Since lipid species with odd carbon chain lengths are rare in mammalian tissue, we decided to discard the odd chained PS annotations. However, some studies reported the presence of PS species with an odd chain length in mammalian tissues, which suggests that they may occasionally be present [52,70]. Furthermore, in negative ionization mode, chloride adducts can be formed from two stable chlorine isotopes 35 Cl and 37 Cl.…”
Section: Limitationsmentioning
confidence: 99%
“…The accumulation of LPA(18:1) is considered a risk factor of atherosclerosis development and it is related to an increased content of macrophages and enhanced oxidative stress, 33,35 which is in line with our results. The presence of increased concentrations of tissue LPA(18:1) has been related to vascular injury in an apoe −/− atherosclerotic model, 36 and here we complete this valuable information with the specific location in the plaque region. The general role of LPCs in the plaque exerts both proatherogenic and antiatherogenic roles depending on the inflammation and oxidative stress status.…”
Section: Lipid Accumulation During Intima Thickeningmentioning
confidence: 90%
“…To strengthen these findings further, incorporating more diversity by considering both male and female participants and including metabolomics and lipidomics data is important. [340,341] With the increasing output of omics data, integrating different omics datasets with molecular dynamics simulations, CFD simulations, or AI is becoming increasingly important to capture the interplay between biochemical and biomechanical factors involved in disease progression. [342] Machine learning has previously been applied to transcriptomics for diagnostic studies of liver injury and mental illness based on gene expression data, but its application in atherosclerosis remains limited.…”
Section: Advances In Single-cell Omics Technologymentioning
confidence: 99%